Pengaruh Lama Pelayuan dan Pencacahan Daun Serai Wangi (Cymbopogon winterianus Jowitt ex Bor) pada Rendemen dan Mutu Citronella Oil - Gumelar, Ayung Musthafa; Ersan, Ersan; Supriyatdi, Dedi (Politeknik Negeri Lampung, 2022)
Lemongrass plants (Cymbopogon winterianus Jowitt ex Bor), used for their own essential oils through the distillation process. Before distillation process, lemongrass leaves are usually withered to reduce air content, and also reduce their size to be more effectively extraction. The research to study the effect of withering and chopping of citronella leaves before being distilled, on the yield and quality of lemongrass oil produced. The study was conducted in a Randomized Block Design, with factorial arrangement, the first factor withered (0, 1, 2, and 3 x 24 hours) and the second factor was the size of the material (chopped and not chopped). Waterand steam distillation were used. The observations made on the raw material water content, yield, specific gravity, total citronellal, total geraniol, solubility in alcohol, and color. The length of withering affected the yield and total geraniol, the size of the material affected the total geraniol. The length of withering with the size of the material affected the total citronellal, where the total citronellal of the chopped material is higher than the not-chopped, and the longer withering made the total citronellal of citronella oil is higher. The length of withering with the size of the material of citronella leaves does not affect specific gravity, solubility in alcohol, and the color of citronella oil.